Making globalization work - Stiglitz, Joseph E. (New York : W.W. Norton & Co., 2007)
[This book] focuses on policies that truly work, offering fresh new thinking about the questions that shape the globalization debate, including a plan to restructure a global financial system made unstable by America's debt, ideas for how countries can grow without degrading the environment, a framework for free and fair global trade, and much more. Throughout, [the author] reveals that economic globalization continues to outpace both the political structures and the moral sensitivity required to ensure a just and sustainable world. And he makes plain the real work that all nations must undertake to realize that goal. -Dust jacket.
-- Another world is possible -- The promise of development -- Making trade fair -- Patents, profits, and people -- Lifting the resource curse -- Saving the planet -- The multinational corporation -- The burden of debt -- Reforming the global reserve system -- Democratizing globalization.
"With a new afterword"--Cover.
Includes bibliographical references (pages 307-354) and index.
Keywords: Globalization -- Economic aspects; International economic integration; Foreign trade regulation